2004
DOI: 10.1017/s1355617704107121
|View full text |Cite
|
Sign up to set email alerts
|

How do neuropsychologists define cognitive constructs? Further thoughts on limitations of factor analysis used with normal or mixed clinical populations

Abstract: In a recent study, we empirically demonstrated limitations in traditional ways that psychologists have used factor analysis to define cognitive constructs (Delis et al., 2003). Our criticism of factor analysis was not directed at this statistical method per se, but rather at how it has often been employed by psychologists to test cognitive constructs. Specifically, we pointed out shortcomings in using this techniquewith normal or mixed clinical populations. We argued that the factor-analytic studies of memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…On a related note, researchers and clinicians are cautioned against utilizing the factor scores in populations with known cognitive impairments. Indeed, concern has been raised in past research about our ability to generalize factor models from normal to clinical populations, as measurement properties may change in these different groups (Delis, Jacobson, Bondi, Hamilton, & Salmon, 2003;Jacobson, Delis, Hamilton, Bondi, & Salmon, 2004). Future research will examine the factor structure of the UDS3NB in clinical samples, as well as the utility of factor scores in these groups.…”
Section: Limitationsmentioning
confidence: 99%
“…On a related note, researchers and clinicians are cautioned against utilizing the factor scores in populations with known cognitive impairments. Indeed, concern has been raised in past research about our ability to generalize factor models from normal to clinical populations, as measurement properties may change in these different groups (Delis, Jacobson, Bondi, Hamilton, & Salmon, 2003;Jacobson, Delis, Hamilton, Bondi, & Salmon, 2004). Future research will examine the factor structure of the UDS3NB in clinical samples, as well as the utility of factor scores in these groups.…”
Section: Limitationsmentioning
confidence: 99%
“…2 , 3 , 8-10 (Carroll, 1993(Carroll, , 2012Horn & Blankson, 2012;Jacobson et al, 2004). (Morgan, Rothlisberg, McIntoch, & Hunt, 2009;K.…”
mentioning
confidence: 99%
“…A useful instrument should have an underlying structure that reflects diagnostically relevant constructs. However, in contrast to this position, based upon the results of numerous factor analytic studies that failed to differentiate between important immediate and delayed memory constructs, some researchers have suggested that factor analysis should not be implemented to evaluate memory instruments (e.g., see, Delis, Jacobson, Bondi, Hamilton, & Salmon, 2003;Jacobson, Delis, Hamilton, Bondi, & Salmon, 2004;Millis, Malina, Bowers, & Ricker, 1999). The failure of data reduction methods to differentiate between these constructs is related to significant shared variance between immediate and delayed memory tasks (i.e., efficient delayed memory is to a degree dependent upon intact immediate memory).Given the shared variance between immediate and delayed memory tasks, it is inappropriate to expect, and highly unlikely, that corresponding factors would be observed.…”
mentioning
confidence: 99%